2005
DOI: 10.1038/sj.onc.1208630
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic alterations of RB2/p130 tumor suppressor gene in human sporadic retinoblastoma: implications for pathogenesis and therapeutic approach

Abstract: Human retinoblastoma occurs in two forms (familial and sporadic) both due to biallelic mutation of the RB1/p105 gene even if its loss is insufficient for malignancy. We have recently reported that loss of expression of the retinoblastoma-related protein pRb2/p130 correlates with low apoptotic index, suggesting that RB2/p130 gene could be involved in retinoblastoma. Mutational analysis of RB2/ p130 in primary tumors showed a tight correlation between Exon 1 mutations and pRb2/p130 expression level in sporadic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 32 publications
3
37
0
1
Order By: Relevance
“…However, until now, little is known about the correlation between inactivation of Rb2/p130 and tumor development. It has been observed that low levels of Rb2/p130 expression correlate with high malignancy in primary tumors (Susini et al, 2001;Li et al, 2004), but only some cases of mutations or promoter methylations of Rb2/p130 have been published (Cinti et al, 2005;Tosi et al, 2005). Unlike direct genetic or epigenetic inactivation, functional inactivation of signaling pathways involving Rb2/p130 occurs at high frequency in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…However, until now, little is known about the correlation between inactivation of Rb2/p130 and tumor development. It has been observed that low levels of Rb2/p130 expression correlate with high malignancy in primary tumors (Susini et al, 2001;Li et al, 2004), but only some cases of mutations or promoter methylations of Rb2/p130 have been published (Cinti et al, 2005;Tosi et al, 2005). Unlike direct genetic or epigenetic inactivation, functional inactivation of signaling pathways involving Rb2/p130 occurs at high frequency in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…This locus is outside either MRL discussed earlier, but RBL2 has been suspected of playing a role in retinoblastoma. Its expression is commonly lost in retinoblastoma (Bellan et al, 2002;Tosi et al, 2005), including in the progression from retinoma to retinoblastoma (Dimaras et al, submitted), and it is one of the genes that can be ablated along with Rb1 to cause retinal tumor formation in mice (MacPherson et al, 2004). It is commonly hypermethylated in tumors with reduced expression, and when WERI-Rb1 cells are treated with a demethylating agent, RBL2 expression is restored, along with expression of p53, p73, and consequent apoptosis (Tosi et al, 2005).…”
Section: Recurrent Losses On 16qmentioning
confidence: 98%
“…Its expression is commonly lost in retinoblastoma (Bellan et al, 2002;Tosi et al, 2005), including in the progression from retinoma to retinoblastoma (Dimaras et al, submitted), and it is one of the genes that can be ablated along with Rb1 to cause retinal tumor formation in mice (MacPherson et al, 2004). It is commonly hypermethylated in tumors with reduced expression, and when WERI-Rb1 cells are treated with a demethylating agent, RBL2 expression is restored, along with expression of p53, p73, and consequent apoptosis (Tosi et al, 2005). However, the ''mutations'' in the RBL2 gene identified by these authors are polymorphisms that are not unique to tumors (they are present in the Celera normal reference human genome assembly, NW_926462.1), and so are unlikely to have an etiological role in retinoblastoma, although they could serve to modify methylation patterns.…”
Section: Recurrent Losses On 16qmentioning
confidence: 98%
“…This family includes the product of the Rb susceptibility gene, the pRb/p105 protein and the related p107 and pRb2/130 proteins (Mayol et al, 1993;Du and Pogoriler, 2006;Merola et al, 2006). They share the ability to recruit chromatin-remodeling enzymes and their best characterized targets are the members of the E2F/DP family of transcription factors, generally referred to as E2F (Cinti et al, 2005;Tosi et al, 2005;Genovese et al, 2006;Macaluso et al, 2006;Purev et al, 2006). Both pRb2/p130 and p107 are able to bind cdk2/ cyclins A and E (Claudio et al, 1996).…”
Section: Introductionmentioning
confidence: 99%